PENGARUH SIKAP, NORMA SUBYEKTIF DAN KONTROL PERILAKU TERHADAP NIAT BELI KUOTA INTERNET DI KOTA LHOKSEUMAWE - Zahrati, Zahrati; Siregar, Widyana Verawaty; Razif, Razif (Faculty of economcs Universitas Singaperbangsa Karawang, 2022)
This study aims to analyze the effect of attitudes, subjective norms, and behavioral control on internet quota purchase intentions from various providers. The object of this research is the people of Lhokseumawe City who use more than twice the sampling method, namely the Purposive Sampling Technique with a sample of 100 respondents. The results showed that the attitude variable had no significant effect on the purchase intention of internet quota, while the subjective norm variable had a significant effect on the purchase intention of internet quota, behavioral control had a significant effect on the purchase intention of internet quota in the city of Lhokseumawe.